The business or financial models for solar irrigation pumps: unveiling Interconnections, advantages, and trade-offs - Mutum, Lamnganbi; Kuriachen, Philip; Taneja, Garima; MPM Deepa; Sikka, Alok; Ringler, Claudia (International Water Management Institute, 2024)
In pursuit of underscoring the need for a nexus-driven approach in upcoming ventures to effectively manage limited resources, a comprehensive study was undertaken in the Indo-Gangetic plains to assess business and financial models. This exploration delved into four distinct models through intensive Focus Group Discussions (FGDs), totaling 3-4 sessions per model. Notably, the models were interconnected utilizing fuzzy cognitive mapping to visually depict their intricate interdependencies. In conclusion, the SIP model through the PM-KUSUM Scheme proves to be most suitable for large-scale farmers in regions lacking groundwater markets. Conversely, the Guarantee Fund Model provides customized solutions tailored for medium and small-scale farmers. In Bihar, Models SBIG and SBII are notably beneficial for marginal farmers managing small, fragmented land holdings. Moreover, ensuring gender inclusivity in these models underscores the importance of advocating capacity-building strategies, thereby enhancing their efficacy and ensuring equitable benefits for all beneficiaries.